THE MODEL OF THE SPECIALIST: THE NATURE, ENVIRONMENT OF FORMATION - Irina V. Shubina (Статистика и экономика, 2016)
The article is devoted to the problem of formation of model of specialist in the field of ICT in the information society. Main modern approaches to the formation of this model, certain conditions and requirements that apply to it in the learning process. Emphasizes the need for dialectical interaction in this process is activity-based and competency-based approaches.